The Identification of Levels of Concept Understanding Using Three-Tier Multiple Choice Diagnostic Test - Witri Adriani; Syamsurizal Syamsurizal; Ganda Hijrah Selaras; Relsas Yogica (ATRIUM PENDIDIKAN BIOLOGI, 2019)
This research aims at identifiying the levels of concept understanding on virus material at class X, SMA Pertiwi 1 Padang. This is a descriptive research involved 138 students from class X, SMA Pertiwi 1 Padang. This research used Three-Tier Multiple Choice diagnostic test instrument which categorized into three question levels. The results showed that students experienced the highest level of concept understanding on prevented virus infections with 53,87%, then followed with the highest level of  full misconception on the role of the beneficial virus with 36,23%, the highest level of misconception false positive on the different virus and bactery with 12,32%, the highest level of misconception false negative on virus living with 14,49%, the highest level of guessing on virus’ classification with  7,61%, and the highest level of ununderstandable of virus replication’s cycles with 52,18%. Most of students experienced low criteria of the concept material of virus with 34,38%.